PENINGKATAN MUTU PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH (MPMBS) PADA MTsN DI KOTA BENGKULU - Hj. Khairiah; H Syarifuddin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The objective of this research was to describe the implementation of the school-based management quality in achieving the educational quality at the public MTs in Kota Bengkulu. The design of this research used a descriptive one the data were collected by using a set of instrument ; i.e. interview, observationand documentation. The results ahow that the otonomi, responsibility, authority, participation, transparency, accountability, equality, equity and sus- tainability has not yet been optimally applied. So it can be suggested if you want to improve the quality of education then implement the program MPMBS